2015
DOI: 10.1177/0025817215573171
|View full text |Cite
|
Sign up to set email alerts
|

Suicide by injecting lispro insulin with an intravenous cannula

Abstract: Suicide by injecting insulin is not uncommon both in diabetic and non-diabetic people. The victim usually uses an insulin syringe or a traditional syringe attached to a needle for the injection of insulin, of either animal or synthetic origin. We report a case of suicide by a non-diabetic physician by injecting lispro insulin through an intravenous cannula. To the best of our knowledge, the use of an intravenous cannula for the injection of insulin for suicide is unusual and is rarely reported in the medico-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
(21 reference statements)
0
10
0
1
Order By: Relevance
“…Data indicate a significant underestimation of the number of suicide attempts and deaths from deliberate overdose [ 33 , 34 , 54 , 56 ]. Moreover, unsuccessful suicide attempts may sometimes be overlooked by the patient’s relatives and doctors [ 57 ]. From the perspective of forensic science, differentiating an accident from suicide is also often difficult and requires careful investigation [ 58 , 59 , 60 ].…”
Section: Accidents and Suicidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Data indicate a significant underestimation of the number of suicide attempts and deaths from deliberate overdose [ 33 , 34 , 54 , 56 ]. Moreover, unsuccessful suicide attempts may sometimes be overlooked by the patient’s relatives and doctors [ 57 ]. From the perspective of forensic science, differentiating an accident from suicide is also often difficult and requires careful investigation [ 58 , 59 , 60 ].…”
Section: Accidents and Suicidesmentioning
confidence: 99%
“…In addition, diagnosing the disease in its acute stage, combined with a negative perception of the disease in the pediatric population, increases the likelihood of self-destructive thoughts and behaviors, which may be an attempt to draw attention to oneself [ 75 ]. Some scientific publications also include cases of insulin overdose suicide attempts by non-diabetic people; however, they are less common and often concern relatives of diabetics [ 14 , 15 , 39 , 57 , 87 , 88 , 89 , 90 , 91 ]. Special cases are suicide attempts with the use of insulin by medical professionals who know and understand the effects of insulin on the body and its pharmacokinetics, and who have easier access to drugs.…”
Section: Accidents and Suicidesmentioning
confidence: 99%
“…Suicide of a 22-year-old painter who was suffering from depression, intravenously injected 2 cc copper sulfate was reported in India (30). In 2015, Behera et al (17), again reported the suicide of a 30-year-old married female physician who used Insulin Lispro with the help of an intravenous cannula in India. The lady was reportedly found to be depressed before the suicide.…”
Section: Unusual Poisoningmentioning
confidence: 99%
“…[36]Samobójstwo przez wstrzyknięcie sobie insulin nie jest rzadkie zarówno u osób z jak i bez cukrzycy. [37] W rezultacie, ważne staje się aby osoby z cukrzycą były badane w kierunku wystąpienia myśli samobójczych przy występowaniu zaburzeń nastroju. Ze względu na łatwiejszy dostęp do potencjalnie śmiertelnych leków (np.…”
Section: Wpływ Cukrzycy Na Ryzyko Samobójstwaunclassified